Raven [compact disc] - Kelela, 1983- (Warp Records, 2023)
Kelela emerges from the tides of her higher self's oceanic orbit with a fifteen-track, continuous play LP exploring autonomy, belonging and self-renewal as healing. With all the sonic, visual, and physical sensualism that magnetized her early core fanbase, Kelela's new album finds her more certain and at ease with her creative fluidity's exceptionality, no matter how high or wide its waves.